Functionalization-Dependent Cytotoxicity of Silver Nanoparticles: A Comparative Study of Chlorhexidine and Metronidazole Conjugates - Karol P. Steckiewicz; Monika Dmochowska; Elżbieta Megiel; Ewelina Barcińska; Iwona Inkielewicz-Stępniak (Biomolecules, 2025)
This study examines the cytotoxicity of two silver nanoparticle formulations—AgNPs conjugated with chlorhexidine (AgNPs-CHL) and AgNPs conjugated with polyethylene glycol and metronidazole (AgNPs-PEG-MET)—as examples of the surface functionalization of silver nanoparticles with drugs via sulfur–silver bonds and nitrogen–silver interactions. We previously reported the synthesis of these NPs and their efficiency in periodontitis treatment. Here, we analyze the relationships between the cytotoxic mechanisms of AgNPs and their surface chemistry. UV–Vis spectroscopy, dynamic light scattering (DLS), and scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX) were used for physicochemical studies of the conjugates in two environments: aqueous solutions and commonly used cell culture media. Cytotoxicity was assessed in human fetal osteoblasts (hFOB 1.19) and human gingival fibroblasts (HGF-1) through BrdU and LDH assays, ROS detection, cell cycle analysis, apoptosis assays, and protein expression studies. AgNPs-CHL showed aggregation and increased hydrodynamic diameters in the culture medium, while AgNPs-PEG-MET remained stable. Both exhibited concentration-dependent cytotoxicity: AgNPs-CHL at 0.4–10 μg/mL and AgNPs-PEG-MET at 0.75–10 μg/mL. AgNPs-CHL, in which silver surface functionalization was realized via nitrogen–silver interactions, induced significant ROS generation, LDH release, and necroptosis, marked by increased RIP1, RIP3, and MLKL proteins. In the case of AgNPs-PEG-MET, where sulfur–silver bonds combined the drug via a PEG linker, they triggered apoptosis, as evidenced by elevated caspase-2 levels and flow cytometry. These findings highlight that the type of surface functionalization of silver nanoparticles significantly influences their physicochemical behavior and biological effects. Understanding these mechanisms is crucial in designing safer, more effective nanoparticle-based therapies for periodontal and other inflammatory conditions.